2022
DOI: 10.1186/s13054-021-03877-y
|View full text |Cite
|
Sign up to set email alerts
|

Endotheliopathy is associated with slower liberation from mechanical ventilation: a cohort study

Abstract: Background Endotheliopathy is suggested as pivotal pathophysiology of sepsis and trauma-associated organ failure, but its role in acute respiratory failure is not yet determined. We investigated if endotheliopathy biomarkers at ICU admission are associated with illness severity and clinical outcomes in patients with acute respiratory failure requiring mechanical ventilation. Methods We conducted a prospective single-center cohort study including 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…This property cannot be formally tested, but based on the known strong associations between the endotheliopathy biomarkers and illness severity, organ dysfunctions, and all-cause mortality, we suspect that it is met in our data. 16,39,48 This is further backed by the finding that the group with missing samples while still in the ICU seemed to be younger and healthier than the group with complete samples (Appendix S3: Table S6). With missing numbers of this magnitude, we can, however, not exclude the possibility that other unknown factors influence the frequency of missingness (data are "missing not at random").…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This property cannot be formally tested, but based on the known strong associations between the endotheliopathy biomarkers and illness severity, organ dysfunctions, and all-cause mortality, we suspect that it is met in our data. 16,39,48 This is further backed by the finding that the group with missing samples while still in the ICU seemed to be younger and healthier than the group with complete samples (Appendix S3: Table S6). With missing numbers of this magnitude, we can, however, not exclude the possibility that other unknown factors influence the frequency of missingness (data are "missing not at random").…”
Section: Discussionmentioning
confidence: 93%
“…10 It is often implicitly assumed that serial measurements of a biomarker carry information beyond that of a baseline value. Inconsistent with that belief, we found that the subgroups based on the trajectories of Syndecan-1 and sTM did not change from ICU Days 1 through 3, and therefore added limited value beyond that of the baseline values measured at ICU Day 1. sTM is a well-validated biomarker at baseline, 16,38,39 but in two randomized trials, the intervention was not associated with a decrease in sTM levels despite showing promise for reducing mortality. 40,41 In the latter study, the intervention was associated with a small decrease in Syndecan-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is reflected by increased serum levels of markers of endotheliopathy [ 29 ]. Elevated sCD138 and sTM levels predict morbidity and mortality in mechanically ventilated patients [ 30 ]. However, severe and protracted hemoconcentration and hypoalbuminemia are uncommon in these conditions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%